Body Double : The Author Incarnate in the Cinema - Fischer, Lucy (Book collections on Project MUSE., 2012)
"Body Double explores the myriad ways that film artists have represented the creative process. In this highly innovative work, Lucy Fischer draws on a neglected element of auteur studies to show that filmmakers frequently raise questions about the paradoxes of authorship by portraying the onscreen writer. Dealing with such varied topics as the icon of the typewriter, the case of the writer/director, the authoress, and the omnipresent infirm author, she probes the ways in which films can tell a plausible story while contemplating the conditions and theories of their making. By examining many forms of cinema, from Hollywood and the international art cinema to the avant-garde, Fischer considers the gender, age, and mental or physical health of fictionalized writers; the dramatized interaction between artists and their audiences and critics; and the formal play of written words and nonverbal images. By analyzing such movies as Adaptation, Diary of a Country Priest, Naked Lunch, American Splendor, and Irezumi, Fischer tracks the parallels between film author and character, looking not for the creative figure who stands outside the text, but for the one who stands within it as corporeal presence and alter-ego."--Publisher's website